Predictors of the Quality of Life of Informal Carers of Adults on the Autism Spectrum. - Sonido, Marisse T.; Hwang, Ye In; Srasuebkul, Preeyaporn; Trollor, Julian N.; Arnold, Samuel R. C. (Journal of Autism & Developmental Disorders, 2022)
Carers of adults on the autism spectrum often experience high levels of stress, worry, and caregiver burden. There are few studies identifying the predictors of carer mental well-being and none have been conducted in Australia. Data from the Autism Cooperative Research Centre for Living with Autism's Australian Longitudinal Study of Autism in Adulthood was used to test the conceptual model by Sonido et al. (Rev J Autism Dev Disord, 2019, https://doi.org/10.1007/s40489-019-00177-8) by (a) identifying the predictors of mental well-being for carers of adults on the spectrum, (b) using model selection to determine which predictors contribute to the model of best fit, and (c) testing for mediating relationships between the predictors. Several predictors were directly associated with carer psychological quality of life, including carer age, care recipient intellectual disability, and carer intolerance of uncertainty. Model selection strongly supported the inclusion of most clusters from the conceptual model. Some mediating relationships were found, such as care recipient depressive behaviours mediating the relationships between caregiver burden and psychological quality of life. Future studies of the conceptual model will improve understanding of the predictors of carer mental well-being and enable tailored interventions to improve the psychological health of carers of adults on the autism spectrum.